Dextransucrase from Weissella cibaria JAG8 Inhibited by Lysine and Cysteine Specific Inhibitors - Rao, T.J.M.; Goyal, Arun (Current Enzyme Inhibition, 2014)
Dextransucrase isolated from Weissella cibaria JAG8 was subjected to active site mapping analysis by using lysine specific inhibitor viz. pyridoxal-5’-phosphate (PLP) and 2,4,6-trinitrobenzenesulphonic acid (TNBS) gave 98.5% and 98.7% inhibition in enzyme activity at 25 mM concentration respectively. The -NH2 lysine derivative of enzymeinhibitor complex with PLP and TNBS gave absorbance maxima at 325 and 369 nm, respectively. PLP modified dextransucrase on reduction with sodium borohydride led to the formation of N-phosphopyridoxyl lysine complex showed fluorescence maxima at 397 nm indicating that one or more lysine residues present near or at the active site and are essential for enzyme activity. Sucrose, provided protection to the enzyme against inactivation by PLP. The enzyme inactivation caused by cysteine specific inhibitors, DTNB (10 mM) and iodoacetic acid (25 mM) was 98.7% and 98.9%, respectively. Enzyme-inhibitor complexes with DTNB (thio-nitrobenzoate) and iodoacetic acid (thio-acetate) were confirmed by appearance of absorbance maxima at 406 and 323 nm, respectively. These results showed that one or more cysteine residues present near or at the active site and are essential for enzyme activity. Essential cysteine residue at the active site is reported for the first time in dextransucrase.
Keywords: thio-nitrobenzoate